IODINE INTAKE DEFICIENCY AS A KEY PREDICTOR OF STUNTING AMONG ADOLESCENT GIRLS IN COASTAL AREA, MAJENE DISTRICT (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2022)
Adolescence is a period in a lifespan with increased nutrition requirements for supporting optimal growth and reproductive maturation. There is a dearth of studies exploring the risk of stunting among adolescents in coastal areas. Majene Regency is a coastal area that is rich in animal protein sources. However, the stunting prevalence of adolescent girls in this area was relatively high. Therefore, this study aimed to identify the contributing predictors of stunting in adolescent girls. A cross-sectional involving 360 adolescent girls in secondary school was employed. Data were analyzed using the chi-square test and logistic regression with a significance of 5%. The overall prevalence of stunting in adolescent girls was 31.7%. Factors significantly associated with stunting were energy and iodine deficiency and wasting. Adolescent girls with low iodine intake (below RDA) were 1.9 times more likely to be stunted (p= 0.027). This study concluded that the prevalence of stunting among adolescent girls living in this coastal area was a high community nutritional problem. We recommended that nutrition promotion is needed, especially regarding the importance of consuming animal food sourced from the sea and the use of iodised salt fortification to prevent stunting in adolescent girls.
Keywords: Stunting; Adolescent Girls; Coastal Area; iodine intake